Practical approaches to plant volatile analysis - Tholl, Dorothea; Boland, Wilhelm; Hansel, Armin; Loreto, Francesco; Röse, Ursula S.R; Schnitzler, Jörg-Peter (The Plant journal : for cell and molecular biology, 2006)
Plants emit volatile organic compounds (VOCs) that play important roles in their interaction with the environment and have a major impact on atmospheric chemistry. The development of static and dynamic techniques for headspace collection of volatiles in combination with gas chromatography-mass spectrometry analysis has significantly improved our understanding of the biosynthesis and ecology of plant VOCs. Advances in automated analysis of VOCs have allowed the monitoring of fast changes in VOC emissions and facilitated in vivo studies of VOC biosynthesis. This review presents an overview of methods for the analysis of plant VOCs, including their advantages and disadvantages, with a focus on the latest technical developments. It provides guidance on how to select appropriate instrumentation and protocols for biochemical, physiological and ecologically relevant applications. These include headspace analyses of plant VOCs emitted by the whole organism, organs or enzymes as well as advanced on-line analysis methods for simultaneous measurements of VOC emissions with other physiological parameters.